Electrochemical analysis of silane incorporated sodium dodecylbenzene sulphonate: zinc sulphate pre-treatment on mild steel and its effect on epoxy coating performance. (3rd April 2022) - Ismail, I.; Harun, M. K.; Yahya, M. Z. A.
ABSTRACT: Variation of surface chemical energy and its effects on adhesion strength and corrosion protection properties of epoxy coatings of mild steel substrates were studied. Results indicated that pre-treatment with a mixture of 3-glycidoxypropyltrimethoxysilane, sodium dodecylbenzene sulphonates and zinc sulphate inhibitors enhanced the corrosion protection properties of epoxy coating when compared to untreated substrates. The formation of a compact insoluble layer of zinc hydroxide/oxide together with SDBS complex on the mild steel surface was found to affect the adhesion properties and resistance towards cathodic/anodic delamination of epoxy coating. This was primarily caused by the formation of strong interfacial interaction and increased in surface passivation. The findings suggested, adhesion alone plays a little part in preventing underfilm corrosion. The underfilm corrosion activities are determined by surface passivity towards corrosion reactions.